Neuropsychological study in 19 French patients with White‐Sutton syndrome and POGZ mutations. Issue 3 (15th December 2020) - Garde, Aurore; Cornaton, Jenny; Sorlin, Arthur; Moutton, Sébastien; Nicolas, Claire; Juif, Christine; Geneviève, David; Perrin, Laurence; Khau‐Van‐Kien, Philippe; Smol, Thomas; Vincent‐Delorme, Catherine; Isidor, Bertrand; et al.
Abstract: White‐Sutton syndrome is a rare developmental disorder characterized by global developmental delay, intellectual disabilities (ID), and neurobehavioral abnormalities secondary to pathogenic pogo transposable element‐derived protein with zinc finger domain ( POGZ ) variants. The purpose of our study was to describe the neurocognitive phenotype of an unbiased national cohort of patients with identified POGZ pathogenic variants. This study is based on a French collaboration through the AnDDI‐Rares network, and includes 19 patients from 18 families with POGZ pathogenic variants. All clinical data and neuropsychological tests were collected from medical files. Among the 19 patients, 14 patients exhibited ID (six mild, five moderate and three severe). The five remaining patients had learning disabilities and shared a similar neurocognitive profile, including language difficulties, dysexecutive syndrome, attention disorders, slowness, and social difficulties. One patient evaluated for autism was found to have moderate autism spectrum disorder. This study reveals that the cognitive phenotype of patients with POGZ pathogenic variants can range from learning disabilities to severe ID. It highlights that pathogenic variations in the same genes can be reported in a large spectrum of neurocognitive profiles, and that children with learning disabilities could benefit from next generation sequencing techniques. Abstract :